White Helmets: Goals, Activity, and Outcome - Yuri Zinin (Международная аналитика, 2019)
The article deals with the origins and activities of the “White Helmets” (WH) organization in Syria during the crisis of 2013 and up to nowadays. The author rejects the view of the WH as a politically unbiased voluntary formation realizing humanitarian mission and claims that the organization was from the outset inspired externally to support anti-government forces in the Syrian Arab Republic. The article cites data exposing generous financing, various material endorsements and political guardianship provided for the “White Helmets” on the part of Western and a number of Middle East and Gulf sponsors. Analyzed also are the WH methods used to release its media products and perform various activities to cautiously distort the occurring events. The author claims a sinister role played by the WH in trumpeting up accusations the Syrian government troops of chemical attacks by against population of cities Khan Sheikhun and Douma. Later on, these accusations were used as an excuse for the airstrikes of the USA and its alliance partners against Syrian facilities. Summing up the activities of the “White Helmets”, the author puts forward some ideas to counter similar projects.